Efektivitas Sistem Akuntansi Penggajian Guru dan Karyawan Pada MTs Yasti 1 Cisaat - Shabrina, Alifa Mujia (Cantaka: Jurnal Ilmu Ekonomi dan Manajemen, 2025)
This study aims to analyze the effectiveness of the payroll accounting system applied at MTs Yasti 1 Cisaat, a private educational institution under the Tarbiyah Islamiyah Foundation. The method used is a qualitative approach with a descriptive method. Data collection techniques are carried out through observation, in-depth interviews, and documentation of school principals, treasurers, heads of administration, and teachers as key informants. Data analysis was carried out using the Miles and Huberman interactive model which includes data reduction, data presentation, and conclusion drawn. The results of the study show that the payroll accounting system used has run quite effectively, especially in terms of the timeliness of payments, the accuracy of salary calculations and deductions, as well as the completeness of supporting documents such as salary slips and attendance lists. Although it does not yet use a dedicated application-based system, the use of Excel has helped with the efficiency of the calculation process. However, some weaknesses are still found, including the absence of written SOPs, dual functions in management, and the lack of regular internal audits. However, the level of user satisfaction with this payroll system is relatively high. This study recommends the need to strengthen the system through the preparation of standard procedures, the use of accounting information technology, and a clearer separation of work functions to increase the effectiveness and transparency of the payroll system in the educational environment.